Business intelligence application in the natural gas industry: A company case - Şahinbaş, Kevser; Yılmaz, Bünyamin (Springer Science and Business Media Deutschland GmbH, 2021)
Recently, information technology tools have been extensively used to accelerate the flow of data, and huge amounts of data have been generated. Therefore, the advantages of having a large amount of data are quite high, however, the increasing masses of data have caused it more complicated for businesses to make new decisions in the intense competitive environment. One of the most important stages of making strategic decisions is to process the existing raw data correctly and to produce new and meaningful information and opportunities, and to use the produced in a way to meet the needs of the market and the sector. To achieve success in a dynamic and hyper-competitive business environment, organizations need effective and timely business information to maintain their continuity. In this regard, organizations need to integrate the necessary technologies into their business processes. Thanks to a well-designed information system, organizations gain advantages in order to achieve the desired goals. Business intelligence systems provide many benefits to the organizations that use them as a type of information system. The aim of this study is to demonstrate the stages of business intelligence and information technology approaches in the natural gas sector and to evaluate and analyze their applicability. Business intelligence systems assist the organization in corporate performance management, optimizing customer relations and supporting decision making. In addition to these, it provides great convenience to decision-making mechanisms with the reports it presents to the management.
Keywords: Natural Gas Industry; Business Intelligence; Company Case